2020
DOI: 10.9734/jpri/2020/v32i2630846
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Trace Elements Levels in Atrial Fibrillation Patients and Healthy Group

Abstract: Background: The aim of this study is to measure the concentration of Zinc (Zn), copper (Cu)  and selenium (Se) in the blood serum of Atrial Fibrillation (AF) patients as compared to healthy subjects in both genders. Methods: This study, conducted on patients with AF (n = 50) and controls (n = 24) were evaluated by available method. Blood samples were taken from the patients and analysis of trace elements was performed by atomic absorption spectrophotometer. Statistical analyses were done using IBM-SPSS 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This was attributed to differences in nutrition and concurring risk factors. Bazargani et al observed that patients with AF have not only lowered the level of Se but also zinc, while the level of copper decreased [ 108 ].…”
Section: The Application Of Se In the Prevention And Treatment Of Cvdmentioning
confidence: 99%
“…This was attributed to differences in nutrition and concurring risk factors. Bazargani et al observed that patients with AF have not only lowered the level of Se but also zinc, while the level of copper decreased [ 108 ].…”
Section: The Application Of Se In the Prevention And Treatment Of Cvdmentioning
confidence: 99%
“…The importance of trace elements in protein synthesis and integrity of collagen is well documented, and deficits in certain trace elements is being linked to cardiac friability and necrosis of cardiac musculature [7]. As a result, trace element shortage in average adult may have a role in cardiovascular disease.)…”
Section: Introductionmentioning
confidence: 99%